The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages The demand for such amenities as allotments will continue, because of the absorbing interest that they provide. Makeshift and inadequate as many of the wartime social and recreational facilities are, they represent a definite social advance, and every effort should be made to increase and encourage them both during and after the war. The West End of London shows clearly enough that millions still have nothing better to do with their leisure than aimlessly parade the streets, though this pastime may, in part, be a symptom of the emotional tension brought about by five years of indecisive war. 8. Culture. The same argument is used against the social provision of cuitural facilities as is used against the provision of other recreational facilities. According to this argument the people who are capable of appreciating art are free to enjoy it in their own way. In practice, the experience for instance of C.E.M.A., has shown that when the best plays and music are presented to hundreds of workers in factories and hostels (hitherto classed as presumably incapable of appreciating culture) they are enthusiastically received, and intelligently discussed. The members of such audiences were not formerly free to choose to see these plays, because they were not performed at places and 16 15X/2/464/1